Women and agroecology: a diagnosis from municipal public policies - Sansao, Eduarda Camargo; Maniglia, Elisabete [UNESP] (Univ Caxias Sul, Centro Ciencias Comunicacao, 2023)
The National Policy on Agroecology and Organic Production, instituted by Decree no. 7,794 / 2012, aims to articulate policies, programs and actions based on agroecological terms and sustainable development for a healthy diet. Through this scope, it is necessary to observe how the subjects targeted by social policies are involved in the construction of public policies. At the same time, the issue of gender stands out from the perspective that this aspect has implications for the economic and social experiences of women. Based on the observed problem, the objective is to diagnose the relationship between municipal public policies on agroecology and the experience of women from art. 3rd, VII, Decree no. 7,794 / 2012, of the National Policy on Agroecology and Organic Production (PNAPO). To structure the article, the methodologies used are based on bibliographic review, document analysis and study of data collected by the National Articulation of Agroecology. Therefore, we consider that women's social movements were articulators for the construction of the National Policy on Agroecology and Organic Production, with attention to the demands arising from the fight against gender inequalities in agriculture. The report Municipios Agroecologicos e Politicas de Futuro - Iniciativas municipais de apoio a agricultura familiar e a agroecologia e de promocao da seguranca alimentar e nutricional and a survey data table made available for public consultation allowed to form an overview of 34 structured initiatives in Brazil that deal with the intersection between women and agroecology.
Keywords: National Policy on Agroecology and Organic Production; Public policy; Women; Agroecology; Gender